2023
DOI: 10.1111/inm.13173
|View full text |Cite
|
Sign up to set email alerts
|

Recovery college dropout: A qualitative study of external, relational and course‐related dropout drivers in co‐produced mental health care

Abstract: Recovery colleges (RCs) are rapidly spreading across Western countries, and research indicates beneficial outcomes of this co‐produced model of mental health care. Meanwhile, risks of adverse outcomes and RC dropout remain understudied. To address this research gap, we conducted qualitative interviews with 14 participants who dropped out of RC courses in Denmark. This article, adhering to the consolidated criteria for reporting qualitative research (COREQ), presents a typology of the main dropout drivers ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Peers being able to support good relationships between people attending a group can lead to positive outcomes (Aschbrenner et al, 2016). However, some studies have found that this can be hard, with concerns about aspects of group process and other students being a key reason for people dropping out of recovery colleges (Andersen et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Peers being able to support good relationships between people attending a group can lead to positive outcomes (Aschbrenner et al, 2016). However, some studies have found that this can be hard, with concerns about aspects of group process and other students being a key reason for people dropping out of recovery colleges (Andersen et al, 2023).…”
Section: Discussionmentioning
confidence: 99%